Removal of large middle molecules via haemodialysis with medium cut-off membranes at lower blood flow rates: an observational prospective study - Kim, Tae Hoon (BMC Nephrol, 2019)
BACKGROUND: Online haemodiafiltration (OL-HDF) may improve middle molecular clearance in contrast to conventional haemodialysis (HD). However, OL-HDF requires higher convective flows and cannot sufficiently remove large middle molecules. This study evaluated the efficacy of a medium cut-off (MCO) dialyser in removing large middle molecular uraemic toxins and compared it with that of conventional high-flux (HF) dialysers in HD and predilution OL-HDF. METHODS: Six clinically stable HD patients without residual renal function were investigated. Dialyser and treatment efficacies were examined during a single midweek treatment in three consecutive periods: 1) conventional HD using an HF dialyser, 2) OL-HDF using the same HF dialyser, and 3) conventional HD using an MCO dialyser. Treatment efficacy was assessed by calculating the reduction ratio (RR) for β2-microglobulin (β2M), myoglobin, κ and λ free light chains (FLCs), and fibroblast growth factor (FGF)-23 and measuring clearance for FLCs. RESULTS: All three treatments showed comparable RRs for urea, phosphate, creatinine, and uric acid. MCO HD showed greater RRs for myoglobin and λFLC than did HF HD and predilution OL-HDF (myoglobin: 63.1 ± 5.3% vs. 43.5 ± 8.9% and 49.8 ± 7.3%; λFLC: 43.2 ± 5.6% vs. 26.8 ± 4.4% and 33.0 ± 9.2%, respectively; P <  0.001). Conversely, predilution OL-HDF showed the greatest RR for β2M, whereas MCO HD and HF HD showed comparable RRs for β2M (predilution OL-HDF vs. MCO HD: 80.1 ± 4.9% vs. 72.6 ± 3.8%, P = 0.01). There was no significant difference among MCO HD, HF HD, and predilution OL-HDF in the RRs for κFLC (63.2 ± 6.0%, 53.6 ± 15.5%, and 61.5 ± 7.0%, respectively; P = 0.37), and FGF-23 (55.5 ± 20.3%, 34.6 ± 13.1%, and 35.8 ± 23.2%, respectively; P = 0.13). Notably, MCO HD showed improved clearances for FLCs when compared to HF HD or OL-HDF. CONCLUSIONS: MCO HD showed significantly greater RR of large middle molecules and achieved improved clearance for FLCs than conventional HD and OL-HDF, without the need for large convection volumes or high blood flow rates. This would pose as an advantage for elderly HD patients with poor vascular access and HD patients without access to OL-HDF. TRIAL REGISTRATION: Clinical Research Information Service (CRIS): KCT 0003009. The trial was prospectively registered on the 21 Jul 2018.